Karl Polanyi and economics: Polanyi's pendulum in economic science - Kretschmer, Mark (Ordnungspolitische Diskurse, 2019)
Since the crisis of 2008 the liberal market order has been challenged by several (populist) social movements and has become object of political regulation. Whereas in the late 70s and early 80s politics tend to deregulate the market, nowadays deregulation seem to be a synonym for the negative externalities of a free global market. Following Polanyi (The Great Transformation, 1944), societies with market market economies tend to experience a double movement - the Polanyi's Pendulum - between phases in which the policies are designed to restrict the markets or liberalize them. This paper raises the question if these indicated changes have an impact on the economic research topics. Referring to modern Varieties-of-Capitalism literature bibliometric data of the period between 1950 and 2015 are used to analyze if there is a Polanyi's Pendulum within the economic literature. Looking for specific key words, e.g. liberalization, and using correlation analyses and time-series regressions it is possible to determine changes of the topics economists worked on and to identify those economic macro-forces that have been driven these changes. The political development in recent years can be considered as a new swing of Polanyi's pendulum. Economics itself is part of the double movement. A second look at Polanyi's might be fruitful to face present challenges better equipped.
Economics
Keywords: Polanyi's pendulum; bibliometry; double movement; political economy; varieties of capitalism

Markets and Society - Zaman, Asad (Social Science Research Network, 2015)
In face of the strong conflict between market norms and social norms, peaceful co-existence is impossible. In traditional societies, markets were subordinated to society. Modern society emerged via a number of revolutions which made society subordinate to markets. This led to a reversal of traditional values of social cooperation and harmony with nature. Instead, men, nature, society became objects to be exploited for creating profits. A market society generates profits by exploiting men and nature, and requires increasing profits to sustain itself. This process has run into its limits as planetary resources are being destroyed on a scale large enough to threaten the planet. Saving the planet requires reversing the transition to modernity by subordinating markets to society. This is a difficult task.
Economics
Keywords: Great Transformation; The (Book); environmental economics; exploitation; market society

Avez-vous lu Polanyi ? - Maucourant, Jérôme (HAL, 2011)
"Cette étude présente le parcours intellectuel de Karl Polanyi (1886-1964), à la croisée de l'économie, de l'histoire et de la sociologie, et propose une synthèse de l'ensemble de son oeuvre." Postface accessible en ligne : [ http://www.contretemps.eu/lectures/bonnes-feuilles-avez-vous-lu-polanyi-j%C3%A9r%C3%B4me-maucourant-postface ]
Economics; Sociology
Keywords: Great Transformation; The (Book); La Grande Transformation; critique and interpretation; critique et interprétation; libéralisme; économie politique

The Great Transition - Spratt, Stephen; Simms, Andrew; Neitzert, Eva; Collins, Josh-Ryan (New Economics Foundation, 2009)
Maps out a set of solutions to various systemic problems "This report argues that nothing short of a Great Transition to a new economy is necessary and desirable, and also possible. " - We have called the process by which this could happen the Great Transition as a deliberate echo of The Great Transformation, written by Karl Polanyi in the 1940s.1 While in a relatively short report such as this we could not hope to achieve anything remotely comparable to Polanyi’s great work, the scale of the change we need to see is at least the equal of the changes he described. Polanyi analysed how market processes in the industrial revolution had created severe ruptures in the fabric of social life, and argued strongly that we needed to reverse this and nd a balance between the market and the non-market; the private and the public; the individual and the community. We couldn’t agree more, and the need to achieve this is all the more pressing now given the huge environmental problems we face, problems that Polanyi could not have foreseen in 1944 when the world was caught in the bloody conclusions of the Second World War. The most pressing problem facing humanity now is how to share scarce planetary resources in ways that are just, sustainable and support the well-being of us all.
Economics
Keywords: environemntal politics; environmental value; redistribution

Competition in transitional processes: Polanyi & Schumpeter - Hager, Theresa; Heck, Ines; Rath, Johanna (ICAE Working Paper Series, 2021)
We examine parallels and differences in the analyses of societal transition by Karl Polanyi and Joseph A. Schumpeter. We argue that although their understanding of historical processes differs - transformational-political vs. evolutionary-natural - the central mechanism of change they describe is the same. We identify three spheres essential to both authors' works: the economic, the political and the socio-cultural sphere. Polanyi and Schumpeter describe an expansion of the economic sphere culminating in a subordination of the other parts of society. In capitalism this dominance stems from capitalism's emergence as well as the concept of competition. The consequence is a profound change in societal relations. Changes in the socio-cultural sphere in turn produce changes in the political sphere that bring about detrimental consequences for democracy. In our paper we carve out the similarities as well as the differences in the respective theories, clarify the role competition plays therein and discuss the consequences for the political process. We adopt an analytical framework that puts the nearly analogous mechanism of change in the centre. This in turn enables us to make use of the complementarity and to gain valuable insights on the interdependence of capitalism and democracy that can inform trends and phenomena that are currently observed.
Keywords: SCHUMPETER; Joseph Alois; 1883-1950; competition; interdependence

The surplus approach, Polanyi and institutions in economic anthropology and archaeology - Cesaratto, Sergio; Bucchianico, Stefano Di (Department of Economics, University of Siena, 2020)
This paper was inspired long ago by Jared Diamond (1997), and in particular by his extensive use of the concept of economic surplus as the key to the development of civilization. Unfortunately, Diamond does not mention the origin of the concept in classical and pre-classical economics, nor does he pay much attention to debates in economic anthropology about the role of economic analysis in studying primitive and ancient economic formations. These debates were the subject of a recent book by Cedrini & Marchionatti (2017), who dispute the neoclassical “imperialist” attempt to occupy the territory of economic anthropology. The authors rely on the institutionalist background provided by Karl Polanyi and his school and by other anthropologists of similar inspiration. Polanyians, however, fail to complete their institutional analysis by anchoring it to the changing modes of generation and distribution of the economic surplus. Yet their emphasis on the need to introduce institutions from the beginning, when speaking of economic surplus, should be taken into consideration by the classical surplus approach
Economics; Anthropology
Keywords: Marx; Polanyi; Sraffa; economic anthropology; economic archaeology; surplus approach